IWRM and poverty reduction in Malawi: A socio-economic analysis - Mulwafu, Wapulumuka O.; Msosa, Hendrina K. (Physics and chemistry of the earth. Parts A/B/C, 2005)
Like most other countries in the SADC region, Malawi has swiftly endorsed the United Nations Millennium Development Goals. In the water sector, these principles are reflected in the National Water Policy (2004) and in the Malawi Poverty Reduction Strategy Paper (PRSP) (2002) which emphasize three key aspects. First, the articulation of a vision and policy objectives that address development and management of water for productive purposes, conservation and poverty reduction. Second, the recognition of international and regional conventions and agreements on water resources to which Malawi is a signatory, thereby promoting global partnership for development. Third, the provision of mechanisms for monitoring, assessment and development related to watershed management, conservation and the mitigation of floods and droughts. Both the Malawi Poverty Reduction Strategy Paper and the National Water Policy seek to reduce poverty by increasing access to water for domestic and productive purposes. In particular, the MPRSP will focus on constructing and rehabilitating water facilities, extend water supply capacity, promote community-based management and improve water resources conservation and management. In this paper, we examine the challenges of implementing these goals against the background of various institutional reforms in the water sector. We argue that although Malawi has come up with very clear strategies and guidelines for promoting MDGs, a combination of human and financial resources, bedevil the successful implementation of these ideas. In addition, the strategies do not articulate water as a medium for poverty alleviation in a holistic manner. The paper further demonstrates ways in which the promotion of IWRM can facilitate in reducing poverty.